Two-way Flow Coupling in Ice Crystal Icing Simulation - Connolly, J; McGilvray, M; Gillespie, D; Bucknell, A; Parker, L; Jones, G; Collier, B (SAE International, 2019)
Numerous turbofan power-loss events have occurred in high altitude locations in the presence of ice crystals. It is theorized that ice crystals enter the engine core, partially melt in the compressor and then accrete onto stator blade surfaces. This may lead to engine rollback, or shed induced blade damage, surge and/or flameout. The first generation of ice crystal icing predictive models use a single flow field where there is no accretion to calculate particle trajectories and accretion growth rates. Recent work completed at the University of Oxford has created an algorithm to automatically detect the edge of accretion from experimental video data. Using these accretion profiles, numerical simulations were carried out at discrete points in time using a manual meshing process. That work showed that flow field changes caused by a changing accretion profile had significant effects on the collection efficiency of impinging particles, ultimately affecting the mass of accreted ice and its shape. This paper discusses the development of the ICICLE numerical ice crystal icing code to include a fully automated two-way coupling between the accretion profile and flow field solution, to account for these effects. The numerical strategy; geometry redefinition, mesh update and flow field solution are discussed, followed by a comparison to experimental ice accretion of a simple 2D geometry and model predictions with and without flow field updating. The results showed that significant changes in leading edge accretion profiles were numerically predicted when the only the geometry was updated. Further changes then occurred when the flowfield was also updated.